2021
DOI: 10.3389/fvets.2021.670451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alpha-Connexin Carboxyl-Terminal Peptide (aCT1) and Bowman-Birk Protease Inhibitor (BBI) on Canine Oral Mucosal Melanoma (OMM) Cells

Abstract: Oral mucosal melanomas (OMM) are aggressive cancers in dogs, and are good models for human OMM. Gap junctions are composed of connexin units, which may have altered expression patterns and/or subcellular localization in cancer cells. Cell-to-cell communication by gap junctions is often impaired in cancer cells, including in melanomas. Meanwhile, the upregulated expression of the gap junction protein connexin 43 (Cx43) inhibits melanoma progression. The α-connexin carboxyl-terminal (aCT1) peptide reportedly mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Application of aCT1 was shown to increase gap junction size and GJIC [12,44]. Prior work shows the anti-cancer effects of aCT1 in the brain, melanoma, and breast cancer [12,45,46]. These reports suggest that aCT1 may have anti-cancer effects of its own and is quite effective at boosting the impact of other anti-cancer agents when added in combination, consistent with the concept of the bystander effect.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Application of aCT1 was shown to increase gap junction size and GJIC [12,44]. Prior work shows the anti-cancer effects of aCT1 in the brain, melanoma, and breast cancer [12,45,46]. These reports suggest that aCT1 may have anti-cancer effects of its own and is quite effective at boosting the impact of other anti-cancer agents when added in combination, consistent with the concept of the bystander effect.…”
Section: Introductionmentioning
confidence: 60%
“…Numerous studies have evaluated Cx43 in breast cancer or other human cancers but fewer have looked at targeting Cx43 with a targeted agent [39,41]. Only a handful of prior studies evaluated the agent aCT1 for use in cancer [12,46,70]. Prior reports have indicated that the mechanism of action for aCT1 is the binding of ZO-1, leading to gap junction accretion, which promotes GJIC [44].…”
Section: Discussionmentioning
confidence: 99%
“…4-year later, one of its variants, αCT11, was found to have the same or similar properties (e.g., membrane permeable) and biological functions (e.g., modulating Cx43 or ZO-1) as αCT1 . In recent years, numerous studies, especially with αCT1, have been conducted to investigate αCT1′s roles in wound healing, , cardiovascular protection, ,, and as an adjunct therapy for cancer. In terms of αCT­(1/11)’s therapeutic benefits for MI and HF, only a few studies using animal or isolated organs have been reported. In the cryo-injured ventricular model of mouse heart, O’Quinn et al found that methylcellulose patches containing αCT1 adhered to injured heart tissue reduced colocalization of Cx43 and ZO-1, increased intercalated disk association of Cx43 at the injury border zone (IBZ), and showed reductions in cardiac arrhythmias and an increase in depolarization rates in treated hearts relative to controls .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in mouse melanoma models, resveratrol enhances cisplatin’s therapeutic effect through the upregulation of connexin 43 (Cx43) expression [ 4 ]. Previously, we have reported [ 15 ] that Cx43 function is impaired in canine OMM cells. Further research is therefore required to explore the influence of resveratrol on the upregulation of Cx43 in canine OMM cells and consequently an enhancement in cisplatin chemosensitivity.…”
mentioning
confidence: 99%